A bamboo pulp black liquor-derived nitrogen-doped lignin activated carbon aerogel and preparation method thereof
By extracting lignin from the black liquid of bamboo slurry, nitrogen-doped lignin activated carbon aerogel was prepared, which solved the problem of low dye pollutant removal efficiency in the prior art, achieved the effect of efficient adsorption of dyes, and had the advantages of environmental protection and industrial application.
Patent Information
- Application Number
- CN202310947271.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-07-31
AI Technical Summary
The prior art is difficult to efficiently remove dye pollutants, especially at low concentrations, and traditional activated carbon materials have problems of low efficiency and high cost when adsorbing dyes.
Nitrogen-doped lignin activated carbon aerogel was prepared by extracting lignin from the bamboo slurry black liquor, cross-linking and freeze-drying, followed by carbonization at low temperatures and activation at high temperatures. The material has a high specific surface area and porosity, and can effectively adsorb dyes.
It realizes efficient adsorption of dyes, especially at low concentrations, and the preparation process of the material is simple, easy to be industrialized, and has significant environmental benefits.
Smart Images

Figure CN117003238B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of activated carbon aerogel materials, and in particular to a method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor. Background Art
[0002] Dyes are one of the inevitable industrial wastewater pollutants in the development of human society. Their strong physiological toxicity can cause mutations and carcinogenesis, damage the skin and respiratory system of animals, and cause irreversible damage to the liver and kidneys. However, due to economic development, society cannot avoid the need to use a large amount of dyes. In addition, dyes show obvious colors at low concentrations, which leads to impaired photosynthesis and reduces the dissolved oxygen level required for aquatic organisms to breathe. The adsorption method has the advantages of simple operation and low cost, and has great potential in dye removal.
[0003] Activated carbon aerogel has a wide range of applications in oil-water separation, pollutant adsorption, and toxic and harmful gas adsorption due to its rich multi-level pore structure. Activated carbon aerogel has a high specific surface area and porosity, and has high adsorption performance without adding other functional materials, and has become a new type of carbon material.
[0004] The preparation of functionalized activated carbon aerogel using bamboo pulp black liquor as raw material is in line with the development concept of sustainability and green environmental protection. Bamboo pulp black liquor is the waste liquid produced by the traditional bamboo pulp papermaking process in the papermaking industry. These black liquids exist in industrial wastewater and are easily released into the water circle, affecting water resources. Bamboo pulp black liquor is rich in lignin and is an excellent source of raw materials for preparing nitrogen-doped lignin activated carbon aerogel. Extracting lignin from bamboo pulp black liquor to prepare lignin aerogel, and further nitrogen-doping carbonization and activation to prepare nitrogen-doped lignin activated carbon aerogel is not only an effective way to achieve high-value utilization of bamboo pulp black liquor, but also has potential application value in the fields of pollutant or toxic and harmful gas adsorption. The prepared nitrogen-doped lignin activated carbon aerogel is a new type of activated carbon aerogel material with the advantages of low density, continuous pore structure, high specific surface area and high pore volume, and is an excellent adsorbent material. Summary of the invention
[0005] The invention overcomes the shortcomings of the prior art and provides a method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor, comprising the following steps:
[0007] S1, mixing bamboo pulp black liquor and water in a mass ratio of 1:20-30, adjusting the pH value to 3-4 with an acid solution, stirring until lignin is completely precipitated, filtering the precipitated solid, washing with water until neutral, and drying to obtain lignin;
[0008] S2, dissolving the lignin in S1 in an alkaline solution, wherein the concentration of the lignin is 30-50 wt %; cross-linking with a cross-linking agent, and freeze-drying to obtain a lignin activated carbon aerogel;
[0009] S3, carbonizing the lignin activated carbon aerogel in S2 at 300-400° C., adding an activator and a nitrogen-doped modifier, and activating at a high temperature of 800-1000° C. to obtain nitrogen-doped lignin activated carbon aerogel.
[0010] In a preferred embodiment of the present invention, in S1, the acid solution is one of sulfuric acid and hydrochloric acid, the treatment time is 2 to 3 hours, and the treatment temperature is 40 to 60°C.
[0011] In a preferred embodiment of the present invention, in S2, the alkaline solution is potassium hydroxide with a concentration of 5-10 wt%.
[0012] In a preferred embodiment of the present invention, the crosslinking agent is one of maleic anhydride, N,N-methylenebisacrylamide and polyethylene glycol diglycidyl ether, with a concentration of 8 to 15 wt %; the crosslinking temperature is 30 to 60° C., and the crosslinking time is 8 to 24 h.
[0013] In a preferred embodiment of the present invention, in S2, the hydrogel is immersed in water to remove NaOH and part of the uncross-linked lignin, and then freeze-dried at a temperature below -30°C.
[0014] In a preferred embodiment of the present invention, the carbonization time is 0.5 to 2 hours.
[0015] In a preferred embodiment of the present invention, the activator is KOH, NaOH, K 2 CO 3 , H 3 PO 4 , H 2 SO 4 、ZnCl 2 , KCl and FeCl 3 The nitrogen-doping modifier is one of urea and melamine.
[0016] In a preferred embodiment of the present invention, in S3, the mass ratio of the carbonized lignin activated carbon aerogel, the activator and the doping modifier is 1:3-10:1-5.
[0017] In a preferred embodiment of the present invention, the activation is carried out in a nitrogen or argon atmosphere, and the activation heating rate is 2 to 10 min / °C.
[0018] The present invention provides a bamboo pulp black liquor derived nitrogen-doped lignin activated carbon aerogel, which is prepared by the above-mentioned preparation method, and the density of the nitrogen-doped lignin activated carbon aerogel is 10-40 mg / cm 3 , with a specific surface area of 1700~2700m 2 / g, and the adsorption performance of malachite green is 2600~3500mg / g.
[0019] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0020] (1) The present invention extracts lignin from bamboo pulp black liquor by acid precipitation, adds a cross-linking agent to cross-link the lignin, and then uses freeze-drying technology to prepare aerogel; the aerogel is nitrogen-doped, activated and carbonized to obtain nitrogen-doped lignin activated carbon aerogel. The nitrogen-doped lignin activated carbon aerogel material prepared by the present invention has high porosity and high adsorption performance, and the preparation process is simple, easy to apply and industrial production, and has significant environmental benefits. The development of this carbon aerogel further expands the huge potential of nitrogen-doped lignin activated carbon aerogel in the field of adsorption.
[0021] (2) In the present invention, bamboo pulp black liquor in the bamboo pulp papermaking industry is used as raw material. The lignin itself is rich in functional groups such as -OH and -COOH. The prepared activated carbon material contains more surface oxygen-containing functional groups and has better adsorption performance, which is of great significance for the recycling of bamboo pulp black liquor.
[0022] (3) In the present invention, the lignin activated carbon aerogel is carbonized at 300-400°C. The lower carbonization temperature helps to generate small and relatively uniform pores, thereby increasing the porosity and surface area of the lignin activated carbon aerogel; some functional groups, such as -OH and -COOH, are retained in the pyrolysis products of the lignin activated carbon aerogel. These functional groups can provide different chemical reaction sites, which help to adsorb specific molecules. Compared with the carbonization process at a higher temperature, the selection of a lower temperature for carbonization saves energy costs and reduces the by-products that may be produced during the carbonization process.
[0023] (4) The carbonized lignin activated carbon aerogel, activator and doping modifier of the present invention are activated at a high temperature of 800 to 1000°C to change their pore structure and surface chemical properties. The high temperature activation can further increase the porosity of the carbonized lignin activated carbon aerogel, enlarge the pore size, and increase the functional groups or active sites on the surface, thereby further improving the adsorption capacity of the lignin activated carbon aerogel.
[0024] (5) The lignin activated carbon aerogel in the present invention has a rich three-dimensional pore structure and specific surface area, which enhances the adsorption active sites for pollutants; by nitrogen doping the lignin activated carbon aerogel, its surface alkaline functional groups are effectively increased, thereby promoting its adsorption performance for cationic dyes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a scanning electron microscope image of the nitrogen-doped lignin activated carbon aerogel prepared in Example 1 of the present invention;
[0027] Figure 2 The pseudo-first-order and pseudo-second-order kinetic models were fitted for the adsorption kinetics of MG by the nitrogen-doped lignin activated carbon aerogel prepared in Example 1 of the present invention;
[0028] Figure 3 This is a graph showing the adsorption performance of malachite green by the nitrogen-doped lignin activated carbon aerogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0031] A method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor comprises the following steps:
[0032] S1, mixing bamboo pulp black liquor and water in a mass ratio of 1:20-30, adjusting the pH value to 3-4 with an acid solution, stirring until lignin is completely precipitated, filtering the precipitated solid, washing with water until neutral, and drying to obtain lignin;
[0033] S2, dissolving the lignin in S1 in an alkaline solution, wherein the concentration of the lignin is 30-50 wt %; cross-linking with a cross-linking agent, and freeze-drying to obtain a lignin activated carbon aerogel;
[0034] S3, carbonizing the lignin activated carbon aerogel in S2 at 300-400° C., adding an activator and a nitrogen-doped modifier, and activating at a high temperature of 800-1000° C. to obtain nitrogen-doped lignin activated carbon aerogel.
[0035] The bamboo pulp black liquor in the present invention comes from Huanlong New Materials Co., Ltd. (Zhejiang, China), and the solid content of the black liquor is 70-80%. Other raw materials include: sulfuric acid, hydrochloric acid, activator, urea and melamine, which are conventional raw materials and are known in the art and will not be described here.
[0036] In S1 of the present invention, in the process of extracting lignin from bamboo pulp black liquor by acid precipitation, the acid solution is one of concentrated sulfuric acid and concentrated hydrochloric acid, wherein the concentrated sulfuric acid is a sulfuric acid solution with a concentration of not less than 70%, and the concentration of concentrated hydrochloric acid is 36%-38%. The acid precipitation treatment time is 2-3 hours, and the treatment temperature is 40-60°C. The precipitated solid is filtered and washed with deionized water until neutral, and dried at 60°C for 12 hours to obtain lignin.
[0037] In the present invention S2, the alkaline solution is potassium hydroxide with a concentration of 5-10wt%; the crosslinking agent is one of maleic anhydride, N,N-methylenebisacrylamide and polyethylene glycol diglycidyl ether with a concentration of 8-15wt%; the crosslinking temperature is 30-60°C and the crosslinking time is 8-24h. The hydrogel is immersed in deionized water to remove NaOH and part of the uncrosslinked lignin, and then freeze-dried at below -30°C.
[0038] In S3 of the present invention, the lignin activated carbon aerogel is carbonized at 300-400° C. for 0.5-2 h. A lower carbonization temperature helps to generate small and relatively uniform pores, thereby increasing the porosity and surface area of the lignin activated carbon aerogel. The pyrolysis products of the lignin activated carbon aerogel retain some functional groups, such as -OH and -COOH, which can provide different chemical reaction sites and help to adsorb specific molecules. Compared with a carbonization process at a higher temperature, selecting a lower temperature for carbonization can save energy costs and reduce by-products that may be produced during the carbonization process.
[0039] The activator of the present invention is KOH, NaOH, K 2 CO 3 , H 3 PO 4 , H 2 SO 4 、ZnCl 2 , KCl and FeCl 3The mass ratio of the carbonized lignin activated carbon aerogel, the activator and the doping modifier is 1:3-10:1-5.
[0040] The activation of the present invention is carried out in a nitrogen or argon atmosphere, the activation heating rate is 2 to 10 min / °C, the carbonized lignin activated carbon aerogel, the activator and the doping modifier are activated at a high temperature of 800 to 1000°C to change the pore structure and surface chemical properties thereof, and the high temperature activation can further increase the porosity of the carbonized lignin activated carbon aerogel, enlarge the pore size, and increase the functional groups or active sites on the surface, thereby further improving the adsorption capacity of the lignin activated carbon aerogel.
[0041] The lignin activated carbon aerogel in the present invention has a rich three-dimensional pore structure and specific surface area, which enhances the adsorption active sites for pollutants; by nitrogen doping the lignin activated carbon aerogel, the alkaline functional groups on its surface are effectively increased, thereby promoting its adsorption performance for cationic dyes.
[0042] The present invention provides a bamboo pulp black liquor derived nitrogen-doped lignin activated carbon aerogel, which is prepared by the above-mentioned preparation method. The density of the nitrogen-doped lignin activated carbon aerogel is 10-40 mg / cm 3 , with a specific surface area of 1700~2700m 2 / g, and the adsorption performance of malachite green is 2600~3500mg / g.
[0043] Example 1
[0044] S1, weigh bamboo pulp black liquor and water in a mass ratio of 1:25, adjust the pH value to 3 with concentrated sulfuric acid, the temperature is 50°C, stir for 2h to completely precipitate lignin, filter the precipitated solid and wash with water to neutrality, and dry at 85°C for 12h to obtain lignin;
[0045] S2, take 8g of lignin in S1, add it to 20ml of water, then add 2.64g of NaOH, and stir evenly; add 4g of polyethylene glycol diglycidyl ether to the completely dissolved lignin solution, cross-link at 60°C for 24h to obtain lignin hydrogel, immerse the hydrogel in water to remove NaOH and part of the uncross-linked lignin, and freeze-dry at -30°C to obtain lignin activated carbon aerogel;
[0046] S3. Carbonize the lignin activated carbon aerogel obtained in S2 at 300°C, and soak the carbonized lignin activated carbon aerogel in water containing KOH and urea, with the mass ratio of aerogel, KOH and urea being 1:4:2, and shake for 24 hours; after drying, put it into a tubular furnace, and heat it to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and maintain it for 1 hour, wash the obtained product with dilute hydrochloric acid and water to remove residual KOH, and obtain nitrogen-doped lignin activated carbon aerogel (NLACA-2) after drying.
[0047] Control group
[0048] The control group was based on Example 1, except that no urea was added during the S3 activation process of the lignin activated carbon aerogel (LACA).
[0049] The present invention conducts morphological characterization and analysis on the preparation of nitrogen-doped lignin activated carbon gas condensation. Figure 1 (a) shows a physical picture of lignin aerogel. Figure 1 (b) is the electron microscope scanning image of lignin aerogel. Figure 1 (c) is a real picture of nitrogen-doped lignin activated carbon aerogel. Figure 1 (d) is a scanning electron microscope image of nitrogen-doped lignin activated carbon aerogel. It can be clearly seen in the image that the surface color of the aerogel is black and the surface is rough, which indicates that the nitrogen-doped lignin activated carbon is successfully combined.
[0050] Figure 2 In the experiment, the pseudo-first-order and pseudo-second-order kinetic models were fitted to the adsorption kinetics of MG at an adsorption temperature of 298K.
[0051] The adsorption kinetics of LACA and NLACA-2 on MG were analyzed using pseudo first-order and pseudo second-order kinetic models according to equations (1) and (2), respectively; where equation (1) is: Formula (2) is Among them, q t (mg / g) is the amount of MG adsorption at t (min), q e (mg / g) is the amount of MG adsorbed at equilibrium. K1(min -1 ) is the pseudo-first-order adsorption rate constant. K 2 (min -1 ) is the pseudo-secondary adsorption rate constant.
[0052] It can be observed that the adsorption of MG by LACA and NLACA-2 increased sharply within 12 h due to pore filling, and the adsorption increased slowly after 12 h until equilibrium was reached, indicating that the prepared adsorbents have good adsorption capacity. The R2 values of the pseudo-first-order kinetic equations of LACA and NLACA-2 are 0.94 and 0.93, respectively, while the R2 values of the pseudo-second-order kinetic equations are 0.97 and 0.9, respectively. Therefore, the pseudo-second-order kinetic model is suitable for describing the adsorption kinetics of MG on LACA and NLACA-2. The above results indicate that the adsorption process is not a single physical adsorption process, but a comprehensive physical and chemical adsorption process dominated by chemical adsorption.
[0053] Figure 3 In the figure, the adsorption performance of the nitrogen-doped lignin activated carbon aerogel prepared in Example 1 of the present invention for malachite green is shown. The Langmuir adsorption isotherm and Freundlich adsorption isotherm were used to analyze the adsorption mechanism of LACA and NLACA-2 for MG at an adsorption temperature of 298K. The Langmuir isotherm assumes that the adsorbate is uniformly covered on the surface of the adsorbent in a monolayer. The Langmuir equation refers to the reference equation (3). Wherein, equation (3) is
[0054] Qe (mg / g) is the amount of adsorption per unit mass of the adsorbent at equilibrium. Qo (mg / g) is the maximum adsorption capacity. Kt (L / mg) is the Langmuir adsorption constant, and Ce (mg / L) is the equilibrium concentration of MG. The Freundlich isotherm assumes that there are multiple layers of coverage on the adsorbent surface. The Freundlich equation refers to equation (4), which is
[0055] Qe (mg / g) is the amount of adsorbent adsorbed per unit mass in equilibrium. Ce (mg / L) is the equilibrium concentration. n and KF are Freundlich constants, which are the adsorption intensity and adsorption capacity of the adsorbent, respectively. Freundlich and Langmuir models were used to fit the adsorption isotherms. With the increase of the initial concentration of MG, the adsorption capacity of LACA and NLACA-2 increased. The R2 values of MG calculated by the Langmuir model (LACA: 0.98; NLACA-2: 0.99) were higher than those of the Freundlich model (LACA: 0.95; NLACA-2: 0.96). The Langmuir model is more comprehensive about the adsorption of MG by LACA and NLACA-2, indicating that monolayer adsorption plays a major role in the adsorption of MG on LACA and NLACA-2.
[0056] The present invention performs specific surface area tests on the nitrogen-doped lignin activated carbon aerogel NLACA-2 of Example 1 and the lignin activated carbon aerogel LACA of the control group. The test results are shown in Table 1.
[0057] Table 1 Specific surface area of samples
[0058]
[0059]
[0060] It can be seen from Table 1 above that adding urea during S3 activation can effectively increase the specific surface area of lignin activated carbon aerogel and further enhance it.
[0061] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor, wherein the nitrogen-doped lignin activated carbon aerogel is applied to the adsorption of malachite green, characterized in that: The following steps are involved: S1, mixing bamboo pulp black liquor and water in a mass ratio of 1:20-30, adjusting the pH value to 3-4 with an acid solution, stirring until lignin is completely precipitated, filtering the precipitated solid, washing with water until neutral, and drying to obtain lignin; S2, dissolving the lignin in S1 in an alkaline solution, wherein the concentration of the lignin is 30-50 wt %; cross-linking with a cross-linking agent, and freeze-drying to obtain a lignin activated carbon aerogel; S3, carbonizing the lignin activated carbon aerogel in S2 at 300-400°C, adding KOH and urea, the mass ratio of aerogel, KOH and urea is 1:4:2, and high temperature activation at 800-1000°C to obtain nitrogen-doped lignin activated carbon aerogel.
2. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: In S1, the acid solution is one of sulfuric acid and hydrochloric acid, the treatment time is 2 to 3 hours, and the treatment temperature is 40 to 60°C.
3. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: In the S2, the alkaline solution is potassium hydroxide with a concentration of 5 to 10 wt%.
4. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: The cross-linking agent is one of maleic anhydride, N,N-methylenebisacrylamide and polyethylene glycol diglycidyl ether, with a concentration of 8 to 15 wt %; the cross-linking temperature is 30 to 60 ° C, and the cross-linking time is 8 to 24 h.
5. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: In S2, the hydrogel is soaked in water to remove NaOH and part of the uncrosslinked lignin, and freeze-dried at below -30 °C.
6. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: The carbonization time is 0.5 to 2 h.
7. The method for preparing nitrogen-doped lignin activated carbon aerogel derived from bamboo pulp black liquor according to claim 1, characterized in that: The activation is carried out in a nitrogen or argon atmosphere, and the activation heating rate is 2-10 min / °C.
8. A bamboo pulp black liquor-derived nitrogen-doped lignin activated carbon aerogel, prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The density of the nitrogen-doped lignin activated carbon gasification is 10-40 mg / cm 3 , with a specific surface area of 1700-2700 m 2 / g, and the adsorption performance of malachite green is 2600~3500 mg / g.
Citation Information
Patent Citations
Preparation method of carbon aerogel, carbon aerogel and lithium ion capacitor prepared from same
CN107680833A
Lignin-based high-specific-surface-area nitrogen-doped porous carbon material as well as preparation method and application thereof
CN114408917A